Work environment and leadership style on employee performance: Evidence of work motivation mediation - Kukuh Harianto; Rike Kusuma Wardhani; Kharisma Ayu Hilma Ricza Aziz (Universitas Ahmad Dahlan, 2026)
Employee performance is a key factor in determining organizational effectiveness and productivity. Organizational factors such as the work environment and leadership style are widely recognized as influencing employee performance, both directly and indirectly through psychological mechanisms such as work motivation. This study aims to analyze the effects of the work environment and leadership style on employee performance, with work motivation as a mediating variable, at Bina Bangun Perkasa Kediri Company. This research employs a quantitative causal approach using saturated sampling involving all 34 permanent employees as respondents. Data were collected through questionnaires and analyzed using partial least squares-structural equation modelling with SmartPLS 4. The results show that the work environment does not significantly affect employee performance or work motivation. Leadership style does not directly influence employee performance but significantly affects work motivation, which in turn significantly improves employee performance. Mediation analysis indicates that work motivation mediates the relationship between leadership style and employee performance, but not between the work environment and employee performance. These findings differ from previous studies that generally report a significant influence of the work environment on employee performance through motivation.